POLA-POLA BILIGUALISME MAHASISWA PBSI FKIP UNIVERSITAS PALANGKA RAYA - Ibnu Yustiya Ramadhan; Stefani Ratu Lestariningtyas; Linggua Sanjaya Usop; Paul Diman; Alifiah Nurrachmana (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Bilingualism is a linguistic phenomenon which includes more than one language as communication tool. All of college students in PBSI FKIP UPR (Study of Indonesian Language and Literature from Faculty of Teacher Education and Training in University of Palangka Raya) came from various social backgrounds which make them bilingualists, where they are used to speak in other languages than Indonesian language as mother tounge, which are code-mix or code-switch. In this research, researchers found many reasons for this bilingualism phenomenon in all college students of PBSI FKIP UPR. The results of this research show: 1) There are 2 (two) bilingualism patterns which are diglossic bilingualism patterns, and not-diglossic bilingualism patterns. 2) Factors of choosing and using language of bilingualistic college students depend on the listener, and conversation topics and situations. 3) Challenges for college students of PBSI FKIP UPR as bilinguialists that they are often to experience miscommunications in formal, nonformal, and semiformal situations while communicating, more impacted by family environment, followed by friendship and college environment.